Teknik Modeling Islam Untuk Mencegah Pernikahan Dini Pada Masa Pandemi di Desa Pematung Kecamatan Sakra Barat (Al-INSAN Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
Marriage is a ceremony of binding marriage vows which is celebrated or carried out by two people with the intention of formalizing the marriage bond according to religious norms, legal norms, and social norms. However, some terms mention several types of marriage, including serial marriages, mandatory marriages, and early marriages. However, here the research focuses more on discussing the issue of early marriage which is one of the problems that often occurs in our environment, early marriage is inseparable from the impacts, including health impacts, maternal and child mortality, stunting of babies born, an increasing number of divorces. This type of research uses qualitative where this approach tends to be descriptive, namely in the form of writing and words that make directions in the background have a descriptive research procedure. Then the subjects in this data collection were KUA Sakra Barat and its staff, the Pematung Village Government, religious leaders, community leaders, parents of beneficiaries, and teenagers as beneficiaries. Data collection methods used are interviews, observation, and documentation. The method used by the Pematung Village Government to prevent early marriage is using the Islamic Modeling Technique Strategy where the community, especially parents and teenagers, get benefits such as, a). can provide an understanding of the impact of early marriage, b). can provide new thoughts on youth-related to early marriage. As for the benefits felt by the parents of teenagers, a). provide an understanding of the ideal age limits for marriage, b). provide parents with an understanding of how to prevent early marriage.